Active MMP-8 Quantitative Test as an Adjunctive Tool for Early Diagnosis of Periodontitis - Marcela Hernández; Mauricio Baeza; Ismo T. Räisänen; Johanna Contreras; Taina Tervahartiala; Alejandra Chaparro; Timo Sorsa; Patricia Hernández-Ríos (Diagnostics, 2021)
Periodontitis is a host-mediated bacterial disease that affects the tooth attachment apparatus. Metalloproteinase-8 (MMP-8), a validated biomarker, could aid in clinical diagnosis. This study aimed to evaluate the diagnostic performance of active (a) MMP-8 immunotest versus total (t) MMP-8 ELISA for quantitative real-time diagnosis and assessment of periodontitis severity at the site level. Gingival crevicular fluid (GCF) was sampled from 30 healthy, 42 mild, and 59 severe periodontitis sites from thirty-one volunteers. MMP-8 concentrations were determined by time-resolved immunofluorometric assay (IFMA) and enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed using the STATA package. Both active and total MMP-8-based methods discriminated among sites according to periodontal diagnosis and severity, with a positive correlation between the two tests (p < 0.001). (a) MMP-8 models showed the best performance in receiver operating characteristic (ROC) curves to discriminate between healthy and periodontitis sites (area under the curve [AUC] = 0.89), while (t) MMP-8 demonstrated a high diagnostic precision in the detection of mild from severe periodontitis sites (AUC ≥ 0.80). The use of (a) MMP-8 and (t) MMP-8 could represent a useful adjunctive tool for periodontitis diagnosis and severity. These results support the applicability of new point-of-care methods in the monitoring of high-risk periodontal patients.